Strategy and optimization of good corporate governance function toward Islamic bank credibility in Indonesia: An ANP approach - Rahmayati, Rahmayati; Mujiatun, Siti; Amsari, Syahrul (International Journal of Innovative Research and Scientific Studies, 2025)
Good Corporate Governance (GCG) in banking is an important part of producing optimal performance and creating sustainable, healthy banking conditions. The aim of this research is to optimize the GCG function in Islamic banking operations. This study uses the Analytical Network Process (ANP) and Focus Group Discussions (FGD) with relevant respondents such as the board of commissioners, board of directors of Islamic banks, and regulators. The results of this study indicate that transparency issues are the main criteria in Islamic bank governance, with agency problems being the highest priority. In addition, responsibility issues related to weaknesses in internal control, lack of independence of the Board of Commissioners, and conflicts of interest in the aspect of fairness are also major concerns. This study provides several strategies offered to Islamic Bank stakeholders. The results of this study guide Islamic bank management to focus on strengthening transparency, internal supervision, and the independence of the Board of Commissioners. By improving these aspects, Islamic banks can increase customer credibility, minimize operational risks, and achieve a balance between profitability and compliance with Islamic principles.